2016
DOI: 10.1586/14760584.2016.1157479
|View full text |Cite
|
Sign up to set email alerts
|

Progress and prospects for L2-based human papillomavirus vaccines

Abstract: Summary Human papillomavirus (HPV) is a worldwide public health problem, particularly in resource-limited countries. Fifteen high-risk genital HPV types are sexually transmitted and cause 5% of all cancers worldwide, primarily cervical, anogenital and oropharyngeal carcinomas. Skin HPV types are generally associated with benign disease, but a subset is linked to non-melanoma skin cancer. Licensed HPV vaccines based on virus-like particles (VLPs) derived from L1 major capsid antigen of key high risk HPVs are ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 108 publications
(128 reference statements)
0
12
0
Order By: Relevance
“…The possibility that the BPVL1-E7 fusion DNA design may elicit E7-specific CD8+ T cell response as well as L1-specific T cell and B cell responses as a single DNA construct holds significant translational values. While the currently available HPV-L1 VLP-based prophylactic vaccines, such as Cervarix, Gardasil, and Gardasil-9, are highly effective, their use in many developing countries are impeded by the technically demanding process and high costs associated with VLP vaccine production and the difficulty of storing and maintaining the VLP vaccines (for review see [ 31 33 ]). Kwak et al has previously suggested the potential of HPVL1 DNA vaccines to generate strong L1-specific antibody response comparable to that generated by Gardasil in vivo [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that the BPVL1-E7 fusion DNA design may elicit E7-specific CD8+ T cell response as well as L1-specific T cell and B cell responses as a single DNA construct holds significant translational values. While the currently available HPV-L1 VLP-based prophylactic vaccines, such as Cervarix, Gardasil, and Gardasil-9, are highly effective, their use in many developing countries are impeded by the technically demanding process and high costs associated with VLP vaccine production and the difficulty of storing and maintaining the VLP vaccines (for review see [ 31 33 ]). Kwak et al has previously suggested the potential of HPVL1 DNA vaccines to generate strong L1-specific antibody response comparable to that generated by Gardasil in vivo [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccines targeting the L2 minor capsid antigen revealed particularly strong and long-lasting antibody responses in mice, with a Th2 to Th1 shift in response ( 141 ). VLPs displaying HPV L2 peptides for capsid display, adjuvant ability, and fusion with early HPV antigens or TLR agonists are in development to improve upon licensed HPV vaccines ( 142 ). These vaccines elicit neutralizing antibodies and can block infection with a wide range of HPV types ( 143 ).…”
Section: Hpv Diseasementioning
confidence: 99%
“…This is likely because of the structural context of L2 display on the VLPs, since L2 was displayed on the AB-loop of the PP7 CP, but at the N-terminus of the MS2 CP [191]. A review on HPV vaccine candidates, including RNA phage VLP-based vaccines, was recently published [212]. A malaria vaccine based on MS2 VLPs has also been reported as very promising [213,214].…”
Section: Vaccines and Vaccine Candidatesmentioning
confidence: 99%